Bengali hand sign language recognition using convolutional neural networks - Rumi, Roisul Islam; Hossain, Syed Moazzim; Shahriar, Ahmed; Islam, Ekhwan (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.